Age is just a number: Examining the preservation of cells and soft tissues in Bothriolepis and other Devonian fish - Christopher L. Rogoff; Paul V. Ullmann (PLoS ONE, 2025)
Recent microscopy and proteomic studies demonstrate fossil bones can preserve remarkable palimpsests of cellular and soft tissue evolution, yet it remains unclear if there are temporal limits to such preservation. For instance, it remains unknown if fossil cells and soft tissues can be recovered from fossil bones of the earliest vertebrates from the middle Paleozoic. To test this, we demineralized nine bone fragments of Bothriolepis and other Late Devonian fish. Removal of phosphates from the fossils released numerous microstructures morphologically consistent with vertebrate osteocytes, pieces of blood vessels, and sheets of fibrous bone matrix which were frequently found to exhibit elemental chemistry potentially indicative of partial organic composition. These discoveries extend this style of exceptional preservation to aspidin and dentine and predate all prior reports of similar cellular/soft-tissue preservation in fossil bones by nearly 100 million years, indicating that the geologic age of a fossil specimen is a poor predictor of whether or not it will retain potentially-endogenous microstructures. Thus, the preservation pathways leading to these forms of soft-tissue fossilization likely began contemporaneously with the evolution of vascularized cellular bone in the early Paleozoic.